Communities' attitudes and aspirations towards tourism development. A Test on the environmental impact - Lee, Helen Hui Hui. (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Nowadays, most of the most countries have found out that enviroment impact is one of the strategies form tourism development. However, the countries have to be concerned about how to ensure the enviroment impact will enhance the communities' attitudes and aspirations towards tourism development. the environment impact being studied in this research included environment, environment management practice, conservation of culture heritage, local satisfaction and influence of resources.